Framatome-ANP Experience in Numerical Simulation of Welding - Gilles, Philippe; Pont, Denis; Keim, Elisabeth; Devaux, Josette (European Journal of Computational Mechanics, 2004)
For nuclear reactor manufacturers, ensuring a high quality of welded joints is one of the basic design rules. Qualification of welders, specific procedures, stress relief heat treatments serve efficiently this goal. Numerical simulation of welding adds the capability of assessing residual stresses, distortions, and in a near future quality of welds. Since almost 25 years, Framatome-ANP has been working on numerical simulation of welding to improve predictions and efficiency of computational tools, namely using the worldwide known SYSWELD. The largest part of Framatome-ANP experience in this field relies in the numerous studies performed by German and French teams on industrial components. This paper tries to account for all these efforts, following a presentation oriented on types of problem.